2021
DOI: 10.4236/ajps.2021.121007
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental UV-A and UV-B Affect the Nutritional Quality of Lettuce and Tomato: Health-Promoting Phytochemicals and Essential Nutrients

Abstract: UV radiation plays an important role not only in plant growth and development but also in the accumulation of essential nutrients and health-promoting phytochemicals in plants. The main objective of this study was to examine the effects of supplemental UV-A, UV-B, and UV-AB on the nutritional quality of lettuce (Lactuca sativa, cv. red leaf "New Red Fire" and green leaf "Two Star") and tomato (Solanum lycopersicum L., cv. BHN-589) grown in a greenhouse. Supplemental UV radiation was provided by UV lamps 5 -6 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
3
11
0
1
Order By: Relevance
“…This further suggests that UV plays an important role in the accumulation of phenolic compounds in lettuce. This is consistent with the results from our previous greenhouse study on the same lettuce varieties, which showed that supplementing solar radiation with UV-A enhanced the concentration of many flavonoids in the red leaf 'New Red Fire' lettuce [32]. Additionally, similar observations have been made on red leaf lettuce (Lollo Russo) where increasing levels of UV radiation increased the accumulation of phenolic acids and flavonoids in the leaves [31] and also, in lettuce grown in an open field as opposed to high tunnels [7,16].…”
Section: Individual Phenolic Compounds and Carotenoidssupporting
confidence: 92%
See 1 more Smart Citation
“…This further suggests that UV plays an important role in the accumulation of phenolic compounds in lettuce. This is consistent with the results from our previous greenhouse study on the same lettuce varieties, which showed that supplementing solar radiation with UV-A enhanced the concentration of many flavonoids in the red leaf 'New Red Fire' lettuce [32]. Additionally, similar observations have been made on red leaf lettuce (Lollo Russo) where increasing levels of UV radiation increased the accumulation of phenolic acids and flavonoids in the leaves [31] and also, in lettuce grown in an open field as opposed to high tunnels [7,16].…”
Section: Individual Phenolic Compounds and Carotenoidssupporting
confidence: 92%
“…This may be due to the reduced overall flux of PAR and UV in the high tunnels due to the high tunnel coverings. However, in contrast, in a previous greenhouse study on tomato, Lee et al [32] showed that actually supplementing solar radiation with UV enhanced the accumulation of carotenoids including lycopene, lutein, and ÎČ-carotene in mature tomato fruits.…”
Section: Lettucementioning
confidence: 68%
“…Lettuce is rich in fiber, fatty acids, amino acids, vitamins A, C, E, B1, B2, and B3, proteins, and minerals (Cu, Al, Na, Mg, K and Ca) (Kim et al, 2016). In addition, it has phytochemical compounds (Sofo et al, 2016;Lee et al, 2021), which provide antioxidant properties (Zapata-Vahos et al, 2020). The micronutrients application through the biofortification of crops is a very useful tool not only to increase the amount of minerals, but also, the production of bioactive compounds is considerably improved.…”
Section: Introductionmentioning
confidence: 99%
“…UVB radiation has been reported to induce the production of harmful molecules, such as reactive oxygen species (ROS), thus damaging plant organs and primary metabolites, and reducing photosynthesis, all of which are necessary for plant life [ 38 , 39 ]. In response to UVB stress, plants can activate secondary metabolism, leading to increased levels of secondary metabolites that act as antioxidants by scavenging ROS [ 40 ]. In this study, ABTS analysis showed increased scavenging activities in UVB-treated purple kohlrabi sprouts, compared to purple kohlrabi sprouts grown without UVB treatment.…”
Section: Discussionmentioning
confidence: 99%